2015
DOI: 10.1159/000381664
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin, Cathepsin S, and Cathepsin L, and Their Association with Inflammatory Markers and Mortality in Patients Undergoing Hemodialysis

Abstract: Background/aims: Although both endostatin and cathepsins S have been associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…In this population, endostatin also correlated strongly with eGFR. Moreover, up to fivefold higher endostatin levels have been observed in patients with CKD or ESRD [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this population, endostatin also correlated strongly with eGFR. Moreover, up to fivefold higher endostatin levels have been observed in patients with CKD or ESRD [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney disease (Cohen and Kretzler, 2003 ; Goulet et al, 2004 ; Reiser et al, 2004 ; Sever et al, 2007 ; Bauer et al, 2011 ; Haase et al, 2014 ; Sołtysiak et al, 2014 ; Carlsson et al, 2015 ; Liu et al, 2015 ; Garsen et al, 2016 ; Cao et al, 2017 )…”
Section: Proteases Cathepsinsunclassified
“…Kidney disease (Luhe et al, 2003 ; Aikawa et al, 2009 ; Carlsson et al, 2015 ; Figueiredo et al, 2015 ; Steubl et al, 2017 )…”
Section: Proteases Cathepsinsunclassified
See 1 more Smart Citation
“…Further, Carlsson et al ( 36 ) in a longitudinal cohort study of 207 patients undergoing hemodialysis found that cathepsin S and L were associated with receptors for tumor necrosis factors. The researchers conclude that the high levels of endostatin, cathepsins S and L, and their associations with tumor necrosis factors warrant further studies within this population exploring mortality, and pathways involved in end-stage renal disease.…”
Section: Resultsmentioning
confidence: 99%